Diagnosis and treatment of ectopic pregnancy - Sobstyl, Małgorzata; Tkaczuk-Włach, Joanna; Bednarek, Wiesława; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2012)
Ectopic pregnancy is reported in 1-2% of all pregnancies. Well-known risk factors for an ectopic pregnancy are: pelvic or abdominal surgery, PID, smoking of women in the reproductive age, age over 35 years and the increased use of assisted reproductive technology. The diagnosis in unruptured ectopic pregnancy has improved due to advances in TVS and measurement of serum β-HCG (β human chorionic gonadotrophin) concentration. Ectopic pregnancy treatment depends on the general status of women, the size of the gestation sac, serum β-HCG concentration and patient’s preferences. Expectant management is possible in some cases of ectopic pregnancies.